Ignition Tradition? A Case Study of the Florida State University Athletics Department’s 2014 Logo Redesign - David P. Hedlund; Brian S. Gordon; Masayuki Yoshida; Joseph St. Germain; Marlon McPhatter (Journal of Applied Sports Management, 2018)
Brand marks are important representations of organizations. Over time, due to a variety of reasons, brand marks may cease to be effective representations and require redesign. In recent years, a number of sport organizations have undertaken efforts to design new or update existing brand marks. In this research, a detailed examination of the opinions and intentions of fans, stakeholders, and the public regarding the Florida State University (FSU) Athletic Department’s redesign of FSU’s primary logo is described, assessed, and discussed. Subscribe to JASM
Keywords: Sport organization; brand mark; logo; redesign; fan behavior